Uniwersytecka srebrna edukacja: teoria, praktyka, perspektywy - Kromolicka, Barbara; Kozłowa, Oxana (Studia Edukacyjne, 2023)
One of the tasks carried out for this particular mission of the university is continuing education, which aims to permanently educate people throughout their lives so as, to improve their competences and skills in coping with a changing reality. Education for seniors is part of the ongoing process of lifelong education (LLL) and plays an important role today. Universities if the third age are a developing proposal for activating seniors as part of continuing education. The article presents an educational activity for seniors of the Szczecin Humanities University for Seniors.